Yellow Fever and Public Health in the New South. - Ellis, John H. (The University Press of Kentucky, 2015)
The public health movement in the South began in the wake of a yellow fever epidemic that devastated the lower Mississippi Valley in 1878--a disaster that caused 20,000 deaths and financial losses of nearly 200 million. The full scale of the epidemic and the tentative, troubled southern response to it are for the first time fully examined by John Ellis in this new book. At the national level, southern congressional leaders fought to establish a strong federal health agency, but they were defeated by the young American Public Health Association, which defended states' rights. Local responses and.